توصیؔف تبسّم کی نظم کا وجودی تناظر: The Existential Perspective of the Poem of Tauseef Tabassum (Research Journal Tahqeeqat, 2025)
This study attempts to read Dr. Tauseef tabassum's poem in the context of the poem after 1960. At that time Urdu poem was compared with the tradition of international poem. In the nineteenth century, Kirkgaard questioned the meaning of human life and its meaning in the twentieth century, the wisdom was kept on the status of a manifestation and the existence was kept in front of it. The answers to the bible, science and philosophy remained insufficient for the physical status of the existence. Tauseef tabassum is counted in the modern literature of Pakistan. He was in adolescence at the time of the partition of the colonists, cutting off the difficulties of emigration with the family, saving the child reached rawalpindi, settled here and died in Islamabad. Your personal experience is related to teaching. Tauseef tabassum's poem has the dimension of self and self-exploration due to individual's autonomy and independence. That's why his poems have deep and wide canvas. He took the task of searching for caste from object but in his statement internal passion is attached to individual's autonomy and freedom. The search for the status of the individual beyond the manifestation is found in the search for the knowledge of annihilation. These are the questions of his poem, what is man? What is the meaning of individual What is the form of liberty and autonomy of the imprisoned person in phenomena.